Luna Moth, Actias (=Tropaea) luna (Linneaus) (Insecta: Lepidoptera: Saturniidae: Saturniinae) - Donald W. Hall (EDIS, 2007)
EENY-411, a 7-page illustrated fact sheet by Donald W. Hall, is part of the Featured Creatures collection. It provides information about this beautiful moth with moon-like spots. Includes references. Published by the UF Department of Entomology and Nematology, June 2007.